Aerials and envy - Maddox, Jake (Maddox, Jake. Jake Maddox JV girls., 2018)
Eighth-grader Tamaya Jackson is captain on her gymnastics team, but she sometimes feels like her coach spends a lot more time with the other gymnasts, and that she is expected to do more with less help--and an interview with the local TV station only makes matters worse when it focuses on her and makes her teammates jealous, so somehow Tamaya and the others must pull it all together because a regional competition is coming up fast.